Effect of Hyamine-1622 Cationic Surfactant on Pertraction of Cerium (IV) Cations Through Emulsion Liquid Membranes - Amany T. Kassem; Mahmoud M. S. Ali (Journal of New Developments in Chemistry, 2021)
The present study aims to shed light directly towards the extraction of (IV) cerium ions using
Keywords: Mohammad Tavakkoli